Valorisation of discarded nonwoven polypropylene as potential matrix-phase for thermoplastic-lignocellulose hybrid material engineered for building applications - Echeverria, Claudia A.; Pahlevani, Farshid; Sahajwalla, Veena (Journal of cleaner production, 2020)
Textiles are a global fast-growing highly-abundant complex waste stream constituted by heterogeneous mixtures of polymers, which at the end-of-life routinely are subject to thermal destruction, incineration, or landfill. Alternatively, this study targets the cascading use of these resources within a circular green manufacturing scheme, examining for the first time the utilization of recycled nonwoven textile Polypropylene (PPt), selected from single-use disposable technical-grade garments in the function of matrix-phase; for the development of non-toxic thermoplastic-lignocellulose hybrid sheet materials engineered for building applications. For this purpose two sources of recycled Polypropylene –textile and food packaging– were selected for the comparative analysis between fibrillated and particulate matrices; and wood fibres sourced from furniture manufacturing residual waste were selected as the lignocellulosic disperse-phase, formulated in the ratio of 40/60 wt%, respectively. The hybrid compounds were mechanically micronized, homogenized, and no coupling agent or additives were incorporated. The overall experimental results indicated PPt presented competitive advantages over the particulate polypropylene due to distinctive morphological, microstructural, crystallinity, and chemical variances; which improved the Filler-Matrix interfacial behaviour, increased the hydrophobicity of the blend, as well as facilitated the thermal-processing of the hybrid prototypes during isothermal hot-compression. Consequently, the end-product exhibited peak performance for flexural strength, moisture resistance, and fire-retardant properties, thus, suggesting that disposable technical-grade PP textiles introduce a viable alternative solution for the advancement of multifunctional sustainable building materials manufactured entirely from heterogeneous complex waste mixtures. [Display omitted] •Incineration is the global trend in disposal of single-use technical garment.•Nonwoven polypropylene for medical application is investigated as matrix phase for hybrid material.•Fracture surface revealed enhanced interface in comparison to particulate matrix phase.•Mechanical, moisture, and fire properties were significantly improved with textile matrix.•Multifunctional hybrid material performance is comparable to standard engineered panels.